Pengaruh Curernt Ratio, Debt Equity Ratio, dan Return Equity Ratio Terhadap Harga Saham Pada Perusahaan Pertanian di Bursa Efek Indonesia - Maghfira Eka Rahmawati (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This study aims to determine the effect of the current, debt-to-equity, and return-to-equity ratios on stock prices in agricultural companies on the Indonesia Stock Exchange. This type of research is descriptive quantitative. The data used in this study are secondary data taken from agricultural companies on the Indonesia Stock Exchange for 2015 - 2019 (5 years), where the population is 24 companies, and 20 companies are taken as samples. The analysis model used is multiple linear regression. The classical assumption test uses a data normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test. The sampling technique used purposive sampling, namely selecting samples with specific considerations. The variables in this study are current ratio (CR) as X1, debt equity ratio (DER) as X2, return equity ratio (ROE) as X3 and stock price (Y). Based on the partial test (t-test) results, the current ratio decision significantly affects stock prices. The debt-equity ratio and return-to-equity ratio do not affect stock prices